040 Outcomes following transcatheter aortic valve implantation comparing Edwards SAPIEN with Medtronic CoreValve ReValving system devices: results from the Milan registry. (16th May 2012) - Buchanan, G L; Chieffo, A; Montorfano, M; Maisano, F; Latib, A; Cioni, M; Figini, F; Carlino, M; Covello, R D; Franco, A; Gerli, C; Grimaldi, A; et al.
Abstract : Background: To assess clinical outcomes of transcatheter aortic valve implantation comparing Medtronic CoreValve ReValving System® with Edwards SAPIEN XT. Methods: All consecutive patients in our center with aortic stenosis treated with transfemoral Medtronic CoreValve ReValving System® (MCV) from November 2009 to September 2011 (learning curve patients excluded) or Edwards SAPIEN XT (ESV) from April 2010 to September 2011 when the device became available were included. Results: In total, there were 192 patients in this analysis. The overall mean age was 79.4±8.1 years, logistic EuroSCORE 21.1±15.9% and STS-PROM score 8.8±8.6%. The MCV group consisted of a greater proportion of males (60.3% vs 43.7%; p=0.026) with a corresponding larger aortic annulus size (24.7±2.0 vs 23.4±1.7; p<0.001). The median clinical follow-up length was 171 (IQR 54–357) days. 30-day all cause mortality was 4.0%, myocardial infarction rate 1.0% and stroke 0.5%, with no differences between valve types. Life-threatening bleeding occurred in 14.7% and 11.5% had a major vascular complication. There were no differences in the combined safety endpoint at 30 days (ESV 72.2% vs MCV 71.9%; p=0.936). However, there was a significantly higher rate of device success among the ESV group (98.3% vs 90.4%; p=0.012) with additionally a significantly higher rate of conduction disturbances/arrhythmia (31.5% vs 16.0%; p=0.011) as well as pacemaker implantation (28.8% vs 5.0%; p<0.001) with MCV compared with ESV. Conclusions: In our single center experience, transcatheter aortic valve implantation was a relatively safe and effective procedure utilising both commercially available devices. However, there was an increased incidence of arrhythmia and pacemaker implantation in the MCV group.